2015
DOI: 10.1136/vr.103172
|View full text |Cite
|
Sign up to set email alerts
|

Dog‐appeasing pheromone collars reduce sound‐induced fear and anxiety in beagle dogs: a placebo‐controlled study

Abstract: The objective of the study was to assess the effects of a dog-appeasing pheromone (DAP) collar in reducing sound-induced fear and anxiety in a laboratory model of thunderstorm simulation. Twenty-four beagle dogs naïve to the current test were divided into two treatment groups (DAP and placebo) balanced on their fear score in response to a thunderstorm recording. Each group was then exposed to two additional thunderstorm simulation tests on consecutive days. Dogs were video-assessed by a trained observer on a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…Recently a tendency to use synthetic pheromones to influence animal behavior can be observed and progress in that field can be noted (Gunn-Moore and Cameron 2004, Tod et al 2005, Falewee et al 2006, Frank et al 2010, Landsberg et al 2015. In domestic animals, except for appeasing pheromones which are commercially available for many species, among others research was also focused on sex pheromones (Izard and Vandenbergh 1982, Stevens et al 1982, Nishimura et al 1991, Rekwot et al 2001, Sankar and Archunan 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a tendency to use synthetic pheromones to influence animal behavior can be observed and progress in that field can be noted (Gunn-Moore and Cameron 2004, Tod et al 2005, Falewee et al 2006, Frank et al 2010, Landsberg et al 2015. In domestic animals, except for appeasing pheromones which are commercially available for many species, among others research was also focused on sex pheromones (Izard and Vandenbergh 1982, Stevens et al 1982, Nishimura et al 1991, Rekwot et al 2001, Sankar and Archunan 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we highlight challenges in the process of creating effective scent‐based tools, and reinforce the notion that post‐production management of these tools must explicitly account for the contextual conditions that most often promote success. While our focus is primarily to explain variability in the nature of responses by prey to predator scents – specifically with respect to creating attractants and repellents that can be used in wildlife management and conservation biology – our framework also provides information on other practical uses of scent including zoo‐enrichment scents (Fay & Miller, ; Samuelson et al., ) appeasement and anti‐anxiolytic pheromones (Landsberg et al., ; Osella et al., ), and other behavioural‐modification cues to influence the mood or emotional state of many terrestrial animals (DePorter, ), including humans.…”
Section: Introductionmentioning
confidence: 99%
“…While an analysis of variance indicated no significant treatment or order effect, the number of dogs reducing levels of inactivity during thunderstorm recordings was higher in the treatment group (60%) than in the placebo group (25%)(DePorter et al, 2012). Note, however, that later studies found that many individuals react with an increase, rather than a decrease, in activity to thunderstorm recordings (Gruen et al, 2015; Landsberg et al, 2015a, 2015b).…”
Section: Introductionmentioning
confidence: 86%
“…One study suggested that the use of DAP and noise CDs in combination had higher owner-reported success rates than when either intervention was used alone (Mills et al, 2003). While the above studies were unblinded and did not include a placebo group, a blinded parallel-group placebo controlled study on the effects of DAP collars on the behavior of laboratory beagles during playbacks of thunderstorm recordings concluded that DAP is of potential benefit as an adjunct to a behavior management program (Landsberg et al, 2015a). In this study, observations of active (such as startling, scanning, bolting, pacing, running, circling, digging, climbing, jumping and barking) and global fear scores were significantly lower in the pheromone-treated group compared to the placebo group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation